1996
DOI: 10.2337/diacare.19.10.1122
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia Enhances Monocyte Binding to Endothelial Cells in NIDDM

Abstract: The results suggest that in NIDDM hypertriglyceridemia should be treated to reduce the high risk for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…No mention of vascular complications was made in that study. However, another study did not report increased monocyteendothelial adhesion in normolipidemic type 1 diabetic patients (39); some of the patients in that study did have vascular complications. Thus, although two of the three studies to date have reported increased monocyte adhesion in type 1 diabetes, it needs to be emphasized that all three studies were small (n Ͻ20).…”
Section: Discussionmentioning
confidence: 95%
“…No mention of vascular complications was made in that study. However, another study did not report increased monocyteendothelial adhesion in normolipidemic type 1 diabetic patients (39); some of the patients in that study did have vascular complications. Thus, although two of the three studies to date have reported increased monocyte adhesion in type 1 diabetes, it needs to be emphasized that all three studies were small (n Ͻ20).…”
Section: Discussionmentioning
confidence: 95%
“…Evidence that endothelial LOX-1 supports adhesion of monocytes and is upregulated in diabetes (19 -21) suggests a role for this receptor in the enhanced binding of monocytes documented in patients with diabetes (28,49,50). Previous studies have shown that glucose may contribute to the increased monocyte adherence to endothelium in diabetes (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DNA damage may lead to injury in the endothelium and induce inflammation and, subsequently, the development of atherosclerosis (45). Monocytes from subjects with diabetes have elevated oxidative stress, inflammation response (46), and binding to endothelium compared with cells from individuals without diabetes (47,48). Furthermore, human atherosclerotic plaques showed high levels of DNA damage (49).…”
Section: Discussionmentioning
confidence: 99%